1988
DOI: 10.1093/oxfordjournals.eurheartj.a062505
|View full text |Cite
|
Sign up to set email alerts
|

Direct Fick cardiac output: Are assumed values of oxygen consumption acceptable?

Abstract: The use of assumed values of oxygen consumption has become an accepted practice in the calculation of direct Fick cardiac output. A survey showed that the assumed values in common use were derived from basal metabolic rate studies on normal subjects, a use which may not be valid. We have compared previous assumed values based on basal metabolic rate or cardiac catheterization studies with those obtained by direct measurement in 80 patients (age range 38-78 years) with various cardiac disorders. Comparison of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…Similarly, many of the patients used to derive the Bergstra formula 8 were infants and children with congenital heart disease, possibly confounding the application of these methods in adult patients. Previous studies have demonstrated errors in VȮ 2 estimation using these and other formulae in pediatric [19][20][21][22] and adult [23][24][25] populations. However, these analyses have limitations, including small sample size with homogeneity of patient population, lack of sub-group analysis in determining other variables that may influence errors in estimation, and use fewer analytic methods to explain the errors observed.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, many of the patients used to derive the Bergstra formula 8 were infants and children with congenital heart disease, possibly confounding the application of these methods in adult patients. Previous studies have demonstrated errors in VȮ 2 estimation using these and other formulae in pediatric [19][20][21][22] and adult [23][24][25] populations. However, these analyses have limitations, including small sample size with homogeneity of patient population, lack of sub-group analysis in determining other variables that may influence errors in estimation, and use fewer analytic methods to explain the errors observed.…”
Section: Discussionmentioning
confidence: 94%
“…The indirect Fick method also has limitations that may affect measurement accuracy, most notably the need to estimate V9O 2 , which when estimated erroneously will lead to an error of the same magnitude in the estimation of CO. Other factors that may affect the Fick method include errors in the measurement of oxygen saturations and haemoglobin levels and the variable influence of bronchial and thebesian venous drainage on the mixed venous saturation [26,28,29]. The indirect Fick method, however, is likely to be highly accurate and reliable in assessing percentage changes in CO in response to an acute intervention, since the only value that often changes in response to the intervention is the mixed venous saturation, and thus the other factors that go into the estimation will cancel out when calculating percentage changes in CO. HOEPER et al [26] compared CO measured by TD and by Fick in a cohort of patients with PAH and found that both methods correlated well, and that the presence of TR did not appear to influence the CO as determined by either method.…”
Section: Discussionmentioning
confidence: 99%
“…First, the Fick principal is often applied to determine cardiac output by the use of an estimate of O 2 uptake. This introduces important error, and O 2 uptake should be measured directly at the time of catheterization 17,18 ; dilution methods are appropriate only in the absence of intracardiac shunting. Second, catheterization data represent a snapshot of supine resting hemodynamics at a single moment in time.…”
Section: Diagnosis: Cardiac Catheterizationmentioning
confidence: 99%